Joint reconstruction of Ictal/inter‐ictal SPECT data for improved epileptic foci localization. Issue 4 (April 2017) - Rakvongthai, Yothin; Fahey, Frederic; Borvorntanajanya, Korn; Tepmongkol, Supatporn; Vutrapongwatana, Usanee; Zukotynski, Katherine; El Fakhri, Georges; Ouyang, Jinsong
Abstract : Purpose: To improve the performance for localizing epileptic foci, we have developed a joint ictal/inter‐ictal SPECT reconstruction method in which ictal and inter‐ictal SPECT projections are simultaneously reconstructed to obtain the differential image. Methods: We have developed a SPECT reconstruction method that jointly reconstructs ictal and inter‐ictal SPECT projection data. We performed both phantom and patient studies to evaluate the performance of our joint method for epileptic foci localization as compared with the conventional subtraction method in which the differential image is obtained by subtracting the inter‐ictal image from the co‐registered ictal image. Two low‐noise SPECT projection datasets were acquired using 99m Tc and a Hoffman head phantom at two different positions and orientations. At one of the two phantom locations, a low‐noise dataset was also acquired using a 99m Tc‐filled 3.3‐cm sphere with a cold attenuation background identical to the Hoffman phantom. These three datasets were combined and scaled to mimic low‐noise clinical ictal (three different lesion‐to‐background contrast levels: 1.25, 1.55, and 1.70) and inter‐ictal scans. For each low‐noise dataset, 25 noise realizations were generated by adding Poisson noise to the projections. The mean and standard deviation (SD) of lesion contrast in the differential images were computed using both the conventional subtraction and our joint methods. We also applied both methods to the 35 epileptic patient datasets. Each differential image was presented to two nuclear medicine physicians to localize a lesion and specify a confidence level. The readers' data were analyzed to obtain the localized‐response receiver operating characteristic (LROC) curves for both the subtraction and joint methods. Results: For the phantom study, the difference between the mean lesion contrast in the differential images obtained using the conventional subtraction versus our joint method decreases as the iteration number increases. Compared with the conventional subtraction approach, the SD reduction of lesion contrast at the 10 th iteration using our joint method ranges from 54.7% to 68.2% ( P < 0.0005), and 33.8% to 47.9% ( P < 0.05) for 2 and 4 million total inter‐ictal counts, respectively. In the patient study, our joint method increases the area under LROC from 0.24 to 0.34 and from 0.15 to 0.20 for the first and second reader, respectively. We have demonstrated improved performance of our method as compared to the standard subtraction method currently used in clinical practice. Conclusion: The proposed joint ictal/inter‐ictal reconstruction method yields better performance for epileptic foci localization than the conventional subtraction method.